Incidencia de un acuerdo en la permanencia estudiantil en la UFPS. (Un análisis con tablas y gráficos estadísticos) - Nelly Estupiñán-Roa; Betty Esperanza Solano-Cañas; Zabdiel Rodríguez-Ibarra (Ecomatemático, 2015)
The dropout rate is a latent problem in the institutions of education superior in Colombia, that affects not only the university context but also the socio-economic environment, therefore it is essential to the Ministry of National Education MENU, to promote in the institutions of higher education programs aimed at strengthening the student retention and graduation, thus contributing to the insertion to the field of labor professionals capable of forging a humanist society. Assuming important aspects of the pedagogy such as academic performance, meaningful learning, interaction and teacher commitment, among others. The Universidad Francisco de Paula Santander Cucuta headquarters, located in the city of Cúcuta, Northern Department of growing along , created the program called Agreement 012, selecting a group of students excluded by academic average of the various races that offers the university, this population was excluded from the higher education program completed, was convened by the University to formally enroll through the 012 Agreement by a single time, an academic semester with orientation modules, which allow you to level your performance. The players of this agreement shall be students, teachers and administrative staff.